1971
DOI: 10.1111/j.1751-1097.1971.tb06192.x
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Regulation in Visual Pigment Chromophore: Large Induced Bathochromic Shifts in Retinol and Related Polyenes.*

Abstract: Abstract— Low temperature techniques are used to record spectra of long wavelength absorbing electrochromic species formed from retinol and related compounds. Formation of these electrochromic species is induced either by iodine or trichloroacetic acid which merely act as acids. The electrochromic species are the corresponding carbonium ions of the respective polyenes. The resulting carbonium ions of a given polyene are identical regardless of whether they are formed by iodine or trichloroacetic acid. The mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…600 nm must be due to protonated forms of ATR. In the 600-nm region, the spectra obtained here show a close resemblance to those acquired by Blatz et al (18,19) using retin01 and acids. Hence, the spectral features are assigned to cationic forms of retinal since Blatz et nl.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…600 nm must be due to protonated forms of ATR. In the 600-nm region, the spectra obtained here show a close resemblance to those acquired by Blatz et al (18,19) using retin01 and acids. Hence, the spectral features are assigned to cationic forms of retinal since Blatz et nl.…”
Section: Resultssupporting
confidence: 64%
“…Hence, the spectral features are assigned to cationic forms of retinal since Blatz et nl. (18,19) invoked the presence of retinylic cationsJo explain the bands at ca. 600 nm (viz.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the reengineering of CRABPII into a protein that can bind a non‐native substrate, all‐ trans ‐retinal, as a protonated Schiff base (PSB) [Fig. 2(a)]21, 22 mimicking the binding of 11‐ cis ‐retinal in rhodopsin, the protein responsible for vision 23–33. This redesigned system is a convenient model for studying the stereo‐ electronic principles that govern wavelength regulation and enable color vision.…”
Section: Introductionmentioning
confidence: 99%
“…This was accomplished by treating retinol, retinyl acetate and anhydroretinol with acids a't low temperature, producing their carbocations and detecting them by UV-VIS spectroscopy. Either retinol or retinyl acetate, when treated with H2SOJ, trichloroacetic or other acids, produces the retinylic cation which absorbs strongly at 589 nm (Blatz et al, 1971). For both substrates, carbocation formation proceeds through a similar mechanism: protonation of oxygen resulting in loss of water or acetic acid depending on substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the substrate is anhydroretinol, two separate paths may be followed during carbocation formation, since protonation may occur at either end of the polyene. Protonation at C15 yields the anhydroretinylic cation absorbing at 620 nm; protonation at C4 yields the retinylic cation absorbing at 589 nm (Blatz et al, 1971). Additionally, it was shown that iodine also behaves as an acid under appropriate conditions and forms carbocations having spectra identical to those formed by proton acids (Blatz et ul., 1971).…”
Section: Introductionmentioning
confidence: 99%